2017
DOI: 10.1155/2017/3684971
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variations of Rabbit Corneal Geometrical and Clinical Biomechanical Parameters

Abstract: Purpose To study the variations in corneal clinical biomechanical parameters (CCBP) and corneal geometrical parameters of rabbit in relation to age. Methods Rabbits aged 3, 7, 12, 18, and 24 months were enrolled. Each eye of the rabbits was tested with Ocular Response Analyzer (ORA), Optical Coherence Tomography (OCT), and Pachymeter to obtain the intraocular pressure (IOP): Goldmann-correlated IOP (IOPg) and Corneal Compensated Intraocular Pressure (IOPcc); CCBP: Corneal Hysteresis (CH) and Corneal Resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…In Table 1 , preoperative corneal thickness (CCT, MCT, and PCT) and postoperative CCT were shown. According to our previous research [ 28 ], there was no significant difference between CCT measured by a pachymeter and OCT images, and in this study, we also got no significant difference in results shown in Table 1 . Moreover, CCT measured from OCT images was more accurate in post-LASIK eyes than that measured from other measurements [ 29 ].…”
Section: Resultssupporting
confidence: 67%
“…In Table 1 , preoperative corneal thickness (CCT, MCT, and PCT) and postoperative CCT were shown. According to our previous research [ 28 ], there was no significant difference between CCT measured by a pachymeter and OCT images, and in this study, we also got no significant difference in results shown in Table 1 . Moreover, CCT measured from OCT images was more accurate in post-LASIK eyes than that measured from other measurements [ 29 ].…”
Section: Resultssupporting
confidence: 67%
“…In this study, corneal strip tensile and stress relaxation experiments were carried out on rabbits with different ages to obtain corneal biomechanical properties. The results of the relationship between ORA parameters and age based on the same rabbits were reported in our last research [23]. Combining these results, we can recognize the mechanical interpretation of ORA parameters preliminarily.…”
Section: Introductionsupporting
confidence: 71%
“…All rabbits were anesthetized with 3% pentobarbital sodium (Merck, Germany) at a dose of 1ml/kg and measured with ORA in vivo for 4 times. The details of the methods for ORA measurements on rabbits have been reported in our previous study [23]. The screening condition was “WS>3.5.” After ORA measurements in vivo, corneal strips tensile experiments were performed on Care-IBTC-50 (In-situ Bi-directional Tension & Compression) Testing System (CARE Measurement & Control Corp., Tianjin, China) under room temperature and 9% saline bath environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats in this research are in the young age, so the basically unchanged IPE stiffness of blank-control eyes during 8-week period fits our expectations. There also have been many researches about the age-related changes in the stiffness of ocular tissues such as cornea [ 37 39 ], sclera [ 40 , 41 ], and lens [ 42 , 43 ]. We will be able to perform indentation experiments on IPE of rats from youth to old age.…”
Section: Discussionmentioning
confidence: 99%